2017
DOI: 10.1002/2017je005319
|View full text |Cite
|
Sign up to set email alerts
|

Paleohydrology on Mars constrained by mass balance and mineralogy of pre‐Amazonian sodium chloride lakes

Abstract:  Halite lake deposits suggest very limited water-rock interaction on Early Mars, different to the extensive alteration evident at Gale Crater  Lakes were > 100 m deep and lasted > (10 1 -10 3 ) yr  Punctuated high rates of volcanism raising temperatures above freezing could have supplied the chlorine for the salt deposits

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 110 publications
1
16
0
Order By: Relevance
“…If oxidizing surface water infiltrated the wetlands of semi−arid climates on early Mars, highly reactive oxychlorides (e.g., ClO 3 − ) would have oxidized the subsurface materials, as suggested previously [44,46]. Less reactive Cl − , Na + , and ClO 4 − in infiltrating surface water could have been transported into deep lakes through regional groundwater flows, as proposed by [8]. The previous study estimated a duration of hydrological cycles based on observed thickness of salt deposits, assuming Na + and Cl − were supplied by water-rock reactions using a reactive transport model [8].…”
Section: Implications For Hydrogeochemical Cycles Around Lakes On Earmentioning
confidence: 77%
See 4 more Smart Citations
“…If oxidizing surface water infiltrated the wetlands of semi−arid climates on early Mars, highly reactive oxychlorides (e.g., ClO 3 − ) would have oxidized the subsurface materials, as suggested previously [44,46]. Less reactive Cl − , Na + , and ClO 4 − in infiltrating surface water could have been transported into deep lakes through regional groundwater flows, as proposed by [8]. The previous study estimated a duration of hydrological cycles based on observed thickness of salt deposits, assuming Na + and Cl − were supplied by water-rock reactions using a reactive transport model [8].…”
Section: Implications For Hydrogeochemical Cycles Around Lakes On Earmentioning
confidence: 77%
“…Less reactive Cl − , Na + , and ClO 4 − in infiltrating surface water could have been transported into deep lakes through regional groundwater flows, as proposed by [8]. The previous study estimated a duration of hydrological cycles based on observed thickness of salt deposits, assuming Na + and Cl − were supplied by water-rock reactions using a reactive transport model [8]. The accumulation of pre−existing surface salts into lakes through regional flows, however, could affect the estimation of the duration [8].…”
Section: Implications For Hydrogeochemical Cycles Around Lakes On Earmentioning
confidence: 98%
See 3 more Smart Citations